Analysis of the Role of Digital Leadership in Public Services at the Religious Court of Karawang - Mulia Manda Masyhuroh; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2025)
This study analyzes the role of digital leadership in enhancing public service quality at the Karawang Religious Court. The locus of informants is the Karawang Religious Court. The study population includes all employees of the Religious Court, while the sample consists of five employees, including the Chief Justice of the Religious Court, a Computer Expert, a secretary, a Substitute Registrar, and a Junior Registrar of Litigation. Operational variables of the study include the dimensions of digital attitude and digital leadership ability. Data was collected through interviews, observations, and literature reviews. The data collection methods employed include in-depth interviews, participatory observation, and document analysis. Data analysis methods use the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing/verification. The study found that the implementation of digital technology at the Karawang Religious Court faces major challenges, such as a lack of human resource readiness, inconsistent leadership, and the digital gap in society. Limited understanding among employees, slow adaptation, and suboptimal data utilization hinder performance. The study concludes that the implementation of new technology has not been matched by human resource readiness, leading to a gap in technology implementation and adaptation. The lack of adequate training and guidance hinders the service process, so a more holistic implementation strategy is needed, taking into account technical, human, and organizational aspects to improve the effectiveness of technology use.